STRATEGI PENANGANAN PEMBIAYAAN MURABAHAH BERMASALAH DI KSPPS PERAMBABULAN BABADAN - Yesti Puspitasari; Fatmawati; Saerosa Indah; Umi Hani; Moch Faisal Fahmi (UI Cirebon (Universitas Islam Cirebon), 2021)
All financial institutions, including KSPPS Perambabulan, in providing murabahah financing do not want their financing to be problematic, however problems often arise. This study aims to determine the strategy used by KSPPS Perambabulan Babadan in dealing with problematic murabahah financing. This study uses a qualitative descriptive research method. Methods of data collection is done by using interviews, observation, and documentation. The results showed that KSPPS Perambabulan applied 3R (Restructuring, Rescheduling, Reconditioning) in dealing with problematic murabahah financing. In addition, if the above method does not work well, the cooperative will advise the customer to sell the collateral object, then the customer only needs to pay the principal to the cooperative. The remaining sales are the full rights of the customer. This strategy has been proven to be able to overcome the problematic murabahah financing problems that occur and have a good impact on the customer's responsibility in fulfilling their obligations.